PARENTS PARTICIPATION OF DIGITAL PARENTING SERVICES THROUGH POSYANDU IN RW 004 LEDENG KOTA BANDUNG - Rina Bastian; Musthafa Kamil; Sardin Sardin (Empowerment : Jurnal Ilmiah Program Studi Pendidikan Luar Sekolah, 2020)
This research is motivated by the issue of childcare. Less optimal care causes problems with the child's development. The form of child development is physical health. Improvement of childcare is carried out through posyandu institutions which serve as learning media. This program aims to increase the role of parents in caring for and educating children in the digital age. The purpose of this study was to determine the participation of parents in utilizing digital parenting services. The program that has been implemented facilitates parents to utilize technological sophistication to find information about children's health through training. Health covers include monitoring children's development, nutritional status and immunization schedule for toddlers at all times. The conceptual foundation used in this study is the concept of parental participation, the concept of digital parenting and the concept of health. This research was conducted at RW 004 Ledeng, Bandung using a quantitative approach. The sources of information in this study were parents as active members of the posyandu RW 004. Data collection techniques used interviews and questionnaires. The results showed that there was an increase in parental participation in the use of digital parenting through posyandu on their respective gadgets. Keywords: Parental Participation, Digital Parenting, Children's Health.